Pengusulan Pasangan Calon Presiden Dan Wakil Presiden Sebagai Peserta Pemilu Menurut Undang-Undang Pilpres - Ahmad Farhan Subhi (Jurnal Cita Hukum, 2015)
Abstract : Nomination of the Candidate Pair of President and Vice President For Participants Election According to the Presidential Election Law. Knowing the legal position of the candidates for President and Vice-President and the Political Parties Elections, namely Knowing setting Political Parties in the nomination of the Candidate Election of President and Vice-President and the timing of the nomination of the candidate of President and Vice President based on legal analysis. It is motivated by the lack of rules regarding the nomination of candidates for President and Vice President of the Law No. 42 Year 2008 on the General Election of President and Vice President, namely in the norm of Article 9 and Article 14 paragraph (2) which do not conform to the norms of Section 22E paragraph (3) and the norm of Article 6A paragraph (2) of the Constitution of the Republic of Indonesia (the 1945 NRI 1945).  Abstrak : Pengusulan Pasangan Calon Presiden dan Wakil Presiden Sebagai Peserta Pemilu Menurut Undang-Undang Pilpres. Mengetahui kedudukan hukum calon Presiden dan Wakil Presiden dan Partai Politik Peserta Pemilu, yakni Mengetahui pengaturan Partai Politik Peserta Pemilu dalam pengusulan Calon Presiden dan Wakil Presiden dan pengaturan waktu pengusulan Calon Presiden dan Wakil Presiden berdasarkan analisa hukum. Hal tersebut dilatar belakangi oleh adanya aturan mengenai pengusulan calon Presiden dan Wakil Presiden dalam Undang-Undang Nomor 42 Tahun 2008 Tentang Pemilihan Umum Presiden dan Wakil Presiden, yakni di dalam norma Pasal 9 dan Pasal 14 ayat (2) yang tidak sesuai dengan norma Pasal 22E ayat (3) dan norma Pasal 6A ayat (2) Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 (UUD NRI 1945).  DOI: 10.15408/jch.v2i2.2324